Bar essentials in constitutional law I - Flores, Reynado Lahom (Manila Rex Book Store, 2025)
The Philippine constitution-- The Philippines as a state-- State policies and principles-- National economy and patrimony-- Legislative department-- National economy and patrimony-- Legislative department-- Executive department-- Judicial department-- Constitutional commission
Keywords: Constitutional law -- Philippines